DDT IN THE ENVIRONMENT: SOURCES, POLLUTION PREVENTION STRATEGIES AND HUMAN HEALTH IMPLICATIONS: A COMPREHENSIVE REVIEW - Mohammad Yaqoob Sarfaraz; Abdullah Haqmal (CV. Radja Publika, 2024)
This review addresses the environmental impact of dichlorodiphenyltrichloroethane (DDT), with an emphasis on its origin, monitoring techniques, pollution tactics, and human health consequences. DDT, a persistent organic pollutant, has been extensively used in agriculture and public health, resulting in its broad dispersion in numerous environments. This study examined the basic causes of DDT pollution, including historical use, agricultural runoff, and incorrect disposal procedures. Furthermore, this study investigated solutions for reducing DDT contamination, including regulatory measures, alternative pest control tactics, and safe disposal procedures. The effects of DDT exposure on human health, including its association with cancer, reproductive abnormalities, and neurological damage, have also been investigated. Overall, this study emphasizes the significance of continued efforts to monitor and reduce DDT pollution in order to protect human health and the environment.